Child Protection from Parents Addicted to Narcotics: An Islamic Law Perspective and the Implementation of National Law in Langkat Regency - Azhar Azhar; Faisar Ananda; Zulkarnain Nasution (Madania: Jurnal Kajian Keislaman, 2025)
This study examines child protection in families affected by parental narcotics addiction from the perspective of Islamic law and its implementation in Langkat Regency, Indonesia. Using a normative-empirical legal approach, the research combines analysis of statutory regulations, classical Islamic jurisprudence, and the Compilation of Islamic Law with field data obtained through interviews, observation, and documentation. The findings reveal that Islamic law regards children as a divine trust (amanah) whose protection aligns with the maqâṣid al-syarîʿah, particularly the preservation of life, intellect, and lineage. Parents addicted to narcotics violate both moral and legal obligations, endangering their children’s welfare. Indonesian legislation—particularly Law No. 35 of 2014 on Child Protection and Law No. 35 of 2009 on Narcotics—reflects similar principles, yet implementation in Langkat remains weak due to limited institutional capacity, poor coordination, and social stigma. Consequently, many children experience neglect and insufficient state protection. However, religious leaders and community organizations play a positive role in supporting affected families through preventive and rehabilitative programs. The study concludes that effective child protection requires integrating theological imperatives with national legal frameworks and strengthening community-based implementation. This research contributes to the discourse on harmonizing Islamic jurisprudence and national law to protect vulnerable children within Indonesia’s social and legal context. Penelitian ini mengkaji perlindungan anak dalam keluarga yang terdampak kecanduan narkotika oleh orang tua, ditinjau dari perspektif hukum Islam dan implementasinya di Kabupaten Langkat, Indonesia. Dengan menggunakan pendekatan hukum yuridis-empiris, penelitian ini memadukan analisis terhadap peraturan perundang-undangan, literatur fikih klasik, serta Kompilasi Hukum Islam dengan data lapangan yang diperoleh melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa hukum Islam memandang anak sebagai amanah ilahi (amanah) yang wajib dilindungi sesuai dengan prinsip maqâṣid al-syarîʿah, khususnya pemeliharaan jiwa, akal, dan keturunan. Orang tua pecandu narkotika telah melanggar tanggung jawab moral dan hukum, sehingga mengancam kesejahteraan anak. Peraturan perundang-undangan Indonesia—terutama Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak dan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika—mencerminkan prinsip serupa, namun implementasinya di Langkat masih lemah akibat keterbatasan kapasitas kelembagaan, koordinasi yang kurang, dan stigma sosial. Akibatnya, banyak anak mengalami penelantaran dan minim perlindungan negara. Meskipun demikian, tokoh agama dan lembaga masyarakat memiliki peran positif dalam mendukung keluarga terdampak melalui program pencegahan dan rehabilitasi. Penelitian ini menyimpulkan bahwa perlindungan anak yang efektif memerlukan integrasi antara imperatif teologis dan kerangka hukum nasional, serta penguatan implementasi berbasis komunitas. Kajian ini berkontribusi pada upaya harmonisasi hukum Islam dan hukum nasional dalam melindungi anak-anak rentan di konteks sosial-hukum Indonesia.